Peranan Keluarga Dalam Menanamkan Nilai-Nilai Pendidikan Agama Islam Pada Anak - Jamari Jamari (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
Education to produce quality human beings is very important for people in the fast-paced advancement, especially in the next century. Islamic religious education is expected as a counterweight and control for the behavior of mankind, it seems still not able to play the role as desired. This study is about the role of families in instilling Islamic religious education values ​​in children in the Village District Karangmulyo Tegalsari Banyuwangi. This study used qualitative research methods. To obtain valid data, then using purposive sampling and snowball sampling technique that is choosing the people who are considered most understand and competent with the object in the perusal. Data collection uses observation, interview, and documentation methods. The data obtained then analyzed using reflective data analysis techniques. From the research and data processing obtained can be concluded that the role of families in instilling Islamic religious education values ​​in children in the Village Karangmulyo Tegalsari District Banyuwangi can be said to be quite good. This is because many parents are aware of the responsibilities of their children's education, especially concerning Islamic religious education